Edukasi dan Pemberian Yoga untuk Mengurangi Nyeri Pinggang dan Melatih Pernapasan Akibat Perubahan Postur Pada Ibu Hamil Di Posyandu Panca Marga Gumpang - Fadila, Dhira Rahma; Saharudin, Adinda Afifah; Safitri, Khusnul; Perdana, Suryo Saputra; Pristianto, Arif (Universitas Methodist Indonesia, 2024)
Background: Pregnancy causes physiological and psychological changes in mothers, including back pain. Yoga can help improve physical and mental fitness through relaxed breathing techniques. Objective: Increase pregnant women's understanding of yoga to reduce low back pain and train breathing. Methods: health education and yoga on breathing exercises to relieve low back pain in the community of pregnant women and evaluate knowledge using questionnaires before and after education. Results: The activity was attended by 16 pregnant women in the 2nd and 3rd trimester at Posyandu Panca Marga Gumpang. Conclusion: Education about low back pain and breathing exercises is expected to increase the knowledge of pregnant women and support labor preparation.